2011
DOI: 10.5703/1288284314246
|View full text |Cite
|
Sign up to set email alerts
|

Use of Dynamic Cone Penetration and Clegg Hammer Tests for Quality Control of Roadway Compaction and Construction

Abstract: Soil compaction quality control presently relies on the determination of the in-place compacted dry unit weight, which is then compared with the maximum dry unit weight obtained from a laboratory compaction test. INDOT requires that the in-place dry unit weight for compacted soil be over 95% of the laboratory maximum dry unit weight. In order to determine the in-place dry unit weight, INDOT engineers generally use nuclear gauges, which are hazardous and also costly because of the required safety precautions. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(26 citation statements)
references
References 78 publications
0
26
0
Order By: Relevance
“…Further work still needs to be carried out in the direction of establishment of the scale of fluctuation of compacted soils to further refine the preliminary large-scale testing procedure proposed in this research. Kim et al (2010) 8 Table 2.6 Correlations developed by White et al (2002) 9 Table 4.1 Field testing locations, dates and number of tests performed 13 Table 4.2 Soil grouping criteria 14 Table 4.3 Location codes 14 Table 4.4 Combined test results for fine-grained soils 14 Table 4.5 Combined test results for coarse-grained soils 15 Table 5.1 Field test results for fine-grained soils 18 Table 5.2 Field test results for coarse-grained soils 19 Table 6.1 Index properties of soils tested by Kim et al (2014) 25 Table 6.2 Index properties of soils from the literature 25 Table 6.3 Soil grouping 27 Table 6.4 Tabular form of recommended blow count values for manufactured coarse-grained soils (INDOT jargon5 granular) commonly used by INDOT in earthwork projects 30 Table 6.5 Index properties and corresponding blow counts for 0 to 6 inches of penetration for the soil used in the moisture sensitivity tests performed by INDOT 31 Table 6.6 DCPT correlations 32 Table 6.7 Implementation plan for DCP correlations 32 Table 7.1 Soil group properties 33 Table 7.2 Comparison of parameters of Beta and Normal distributions 37 Table 7.3 Distribution fitting parameters for the field grid testing 39 Table 7.4 Simulation results-percentile and corresponding variances 39 Table 7.5 DCP test results from variability study 41…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Further work still needs to be carried out in the direction of establishment of the scale of fluctuation of compacted soils to further refine the preliminary large-scale testing procedure proposed in this research. Kim et al (2010) 8 Table 2.6 Correlations developed by White et al (2002) 9 Table 4.1 Field testing locations, dates and number of tests performed 13 Table 4.2 Soil grouping criteria 14 Table 4.3 Location codes 14 Table 4.4 Combined test results for fine-grained soils 14 Table 4.5 Combined test results for coarse-grained soils 15 Table 5.1 Field test results for fine-grained soils 18 Table 5.2 Field test results for coarse-grained soils 19 Table 6.1 Index properties of soils tested by Kim et al (2014) 25 Table 6.2 Index properties of soils from the literature 25 Table 6.3 Soil grouping 27 Table 6.4 Tabular form of recommended blow count values for manufactured coarse-grained soils (INDOT jargon5 granular) commonly used by INDOT in earthwork projects 30 Table 6.5 Index properties and corresponding blow counts for 0 to 6 inches of penetration for the soil used in the moisture sensitivity tests performed by INDOT 31 Table 6.6 DCPT correlations 32 Table 6.7 Implementation plan for DCP correlations 32 Table 7.1 Soil group properties 33 Table 7.2 Comparison of parameters of Beta and Normal distributions 37 Table 7.3 Distribution fitting parameters for the field grid testing 39 Table 7.4 Simulation results-percentile and corresponding variances 39 Table 7.5 DCP test results from variability study 41…”
Section: Resultsmentioning
confidence: 99%
“…The data collected strongly indicated that reasonable correlations could be developed between the DCPT blow count required to satisfy INDOTs relative compaction criteria and the controlling soil properties that affect the mechanical response of the soil to the loading by the DCP (Kim et al, 2010). The most important aspects that needed further research were: (1) identification of the main soil groups that showed similar response to the impact loading from the DCP, (2) identification of an individual or a combination of controlling properties that govern the mechanical response of each soil group to loads applied by the DCP, and (3) quantification of the effect of the moisture content of the subgrade soil after compaction on the DCP blow count measured.…”
Section: Problem Statementmentioning
confidence: 99%
See 3 more Smart Citations